2014
DOI: 10.1016/j.scitotenv.2014.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Health concerns and perceptions of central and coastal New Jersey residents in the 100days following Superstorm Sandy

Abstract: Superstorm Sandy made landfall in New Jersey 29–30 October 2012 (80 km/hr winds), and many residents were evacuated, were without power for days to several weeks, and suffered property damages or lost their homes. The objective of this study was to understand health concerns within 100 days of this devastating storm that might improve recovery, future preparedness, and resilience. We conducted a survey of New Jersey residents in central (N = 407) and shore communities (n=347) about health concerns before, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
4
23
1
Order By: Relevance
“…This result was similar with the previous study in New Jersey which indicated that the greatest concerns of residents before the typhoon was possessions and property damage, while during and after the disaster, their major concerns were personal health [34]. In our study, only about half of participants affirmatively express that typhoon might pose threat to their health (50.7%) or life (42.2%), and less than half of the participants (37.4%) expressed a fear of typhoons.…”
Section: Discussionsupporting
confidence: 91%
“…This result was similar with the previous study in New Jersey which indicated that the greatest concerns of residents before the typhoon was possessions and property damage, while during and after the disaster, their major concerns were personal health [34]. In our study, only about half of participants affirmatively express that typhoon might pose threat to their health (50.7%) or life (42.2%), and less than half of the participants (37.4%) expressed a fear of typhoons.…”
Section: Discussionsupporting
confidence: 91%
“…General Linear Models were developed to examine the factors that accounted for variation in the overall ratings for the four main concern categories (including ecological services); independent variables were total days recreating, location, stress-or level, distance to the ocean, age, sex, ethnicity, education, days without electricity and home repairs needed. This paper addresses concerns about ecological and environmental issues; specific health effects data and information sources can be found elsewhere (Burger et al 2013; Burger and Gochfeld 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Specific health effects data and information sources can be found elsewhere (Burger et al 2013; Burger and Gochfeld 2014). The entire questionnaire including several types of information: (1) storm effects (property damage, flooding, evacuation, and loss of power), (2) general concerns before, during, and after Sandy , (3) information sources (used and trusted), (4) health concerns, (5) renovations/repairs and mold, (6) rating of a list of concerns, and (7) demographics.…”
Section: Methodsmentioning
confidence: 99%